HUBUNGAN PERAWATAN KELUARGA DENGAN PERSONAL HYGIENE PADA LANSIA DI DUSUN ASEM NUNGGAL DESA KALIANGET BARAT KECAMATAN KALIANGET - Mujib Hannan; Dian Ika Puspitasari (Wiraraja Medika : Jurnal Kesehatan, 2017)
Family care affects personal hygiene on the elderly this indicates that care family is the family indicator in performing the function of health while the personal hygiene is a parameter that used to improve the care of the family. The aims of this research are to know relationship between the treatment of families with personal hygiene on the elderly in Dusun Asem Nunggal Desa Kalianget Barat Kecamatan Kalianget. This research is quantitative with cross sectional approach. Population are all elderly in Dusun Asem Nunggal Desa Kalianget Barat Kecamatan Kalianget are 56 people. The number of samples are 49 people with simple random sampling. Data analysis using the Spearman Rho to test (α = 0.05 ). Data collection using observation and family care questionnaires and personal hygiene. The results of research on family care shows most (57,1%) do good family care. While the results of research about personal hygiene showed the majority of respondents (61,2%) do personal hygiene well. The results of the test using the corelation of spearman rho indicates p value= 0.000 which means there is a significant relationship between family care with personal hygiene on the elderly. Families can improve the care of the family and understand more about health problems in the elderly. The elderly must maintain personal hygiene on him. The better care the family performed on the elderly then personal hygiene on the elderly is also getting better.